2011
DOI: 10.1371/journal.pone.0023869
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Functional Brain Activation Using [14C]-Iodoantipyrine in Male Serotonin Transporter Knockout Mice

Abstract: BackgroundSerotonin transporter knockout mice have been a powerful tool in understanding the role played by the serotonin transporter in modulating physiological function and behavior. However, little work has examined brain function in this mouse model. We tested the hypothesis that male knockout mice show exaggerated limbic activation during exposure to an emotional stressor, similar to human subjects with genetically reduced transcription of the serotonin transporter.Methodology/Principal FindingsFunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 67 publications
(91 reference statements)
4
31
1
Order By: Relevance
“…However, a clinical study suggests a correlation between the activation of insula and the unpleasantness of tonic pain stimulus (41), and a recent preclinical study showed increased cerebral blood flow in the anterior part of insular cortex during anxiety-like behaviors (42). These observations differ in many variables from present work, such as the type of stimulus (acute versus chronic) or the targeted insular cortex subregion (anterior versus posterior).…”
Section: Discussioncontrasting
confidence: 74%
“…However, a clinical study suggests a correlation between the activation of insula and the unpleasantness of tonic pain stimulus (41), and a recent preclinical study showed increased cerebral blood flow in the anterior part of insular cortex during anxiety-like behaviors (42). These observations differ in many variables from present work, such as the type of stimulus (acute versus chronic) or the targeted insular cortex subregion (anterior versus posterior).…”
Section: Discussioncontrasting
confidence: 74%
“…In analogy with the 5-HTTLPR findings, 5-HTT knockout (5-HTT 2/2 ) rats and mice show-next to increased anxiety-and depression-like behaviors (Kalueff et al 2010)-improved performance in a reversal learning task (Brigman et al 2010;Nonkes et al 2011) and functional changes in prefrontal areas subserving reversal learning (orbitofrontal cortex; OFC) and extradimensional set-shifting (medial prefrontal cortex; mPFC) (Ragozzino 2007;Wellman et al 2007;Nonkes et al 2010;Keeler and Robbins 2011;Pang et al 2011). Therefore we hypothesized that 5-HTT 2/2 rats also show improved extradimensional set-shifting.…”
mentioning
confidence: 83%
“…Specifically, the orbitofrontal cortex (OFC) is implicated in reversal learning (McAlonan and Brown 2003;Ghods-Sharifi et al 2008), the medial prefrontal cortex (mPFC) in extradimensional (strategy) set-shifting (Ragozzino et al 1999;Floresco et al 2008), and latent inhibition paradigms (George et al 2010). As anatomical and task-related functional changes in these regions have been reported in 5-HTT 2/2 rodents (Wellman et al 2007;Nonkes et al 2010;Pang et al 2011), the observed genotype differences in reversal learning (Nonkes et al 2011) and the EDSS and latent inhibition paradigms (present study) might relate to altered OFC and mPFC function. In line, we specifically observed a genotype effect on mPFC-dependent perseverative errors, but not regressive or never-reinforced errors, which are thought to be more striatum-dependent (Floresco et al 2009).…”
mentioning
confidence: 99%
“…Other risk factors such as variation in 5-HTTLPR in humans, that affects the prevalence of several anxiety disorders including PTSD, can be assessed in this model as well [46][47][48] . 5-HTT knockout rats, displaying increased freezing and impaired fear extinction [49][50][51] or fear extinction recall [52][53][54] , have been used as model for the more PTSD-susceptible 5-HTTLPR genotype. The polymorphism results in differences in serotonin regulation that play an important role in anxiety disorders.…”
Section: Yehuda and Antelman's Criteria For Rationally Evaluating Ptsmentioning
confidence: 99%